IMPLEMENTATION OF DIRECTOR GENERAL HEALTH REGULATION ON LOCAL FOOD SUPPLEMENTFOR PREGNANT WOMEN AND TODDLERSTO PREVENT STUNTING - Nur Alim Fatah; Yuly Peristiowati; Ratna Wardani (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background: Stunting is a serious public health issue in Indonesia. To address this, the Directorate General of Public Health issued a technical regulation on the provision of local food-based supplementary feeding for pregnant women and toddlers. This study aims to analyze the implementation of Regulation No. HK.02.02/B/1622/2023 regarding this policy in Kediri Regency. Method: A qualitative case study approach was used, with purposive sampling of key informants including heads of community health centers, nutrition officers, cadres, pregnant women, and mothers of stunted toddlers. Data were collected through observations and interviews in July 2025. Ethical approval was obtained. Result: Findings show that the implementation of the supplementary feeding program using local foods positively contributes to stunting prevention among pregnant women and toddlers in Kediri. Program monitoring is conducted through regular recording, structured reporting, and periodic evaluation. Funding primarily comes from the Health Operational Assistance Fund (BOK), managed transparently by the health centers. Conclusion: the policy has been effectively implemented in several health facilities, making it a strategic effort to combat stunting in Kediri Regency, particularly through the distribution of locally based supplementary food.